Congestion, wage rigidities and the provision of public intermediate goods - Johannes Pauser (ZBW - Leibniz Information Centre for Economics, 2020)
This paper examines efficiency in the provision and utilization of a congestible public input in a symmetric tax competition framework with wage rigidities. Despite the fact that also lump-sum taxation is available for regional governments, second-best efficiency emerges only as a special case in the non-cooperative equilibrium. In the special case with Cobb-Douglas production, the congestion technology can be shown to be crucial for the analysis of efficiency in the decentralized equilibrium. Assuming decreasing marginal congestion, efficiency in the non-cooperative equilibrium is determined alone by the production and congestion elasticities. In contrast, factor prices such as the level of the wage rigidity and corresponding employment levels are, in addition, important to determine whether both provision and utilization levels of the public input are efficient in case of increasing marginal congestion.
Keywords: H41; H21; H25; 330; Fiscal competition; public inputs; wage rigidities; congestion